On the possibility of a systematic study of the production management systems - Kolesnyk, V.G. (PROBLEMS IN PROGRAMMING, 2018)
Degree of similarity between systems, subsystems and tasks of MIS for different industries (the companies, departments, shops) is minimum that generates big expenses in designing of the software. The methodology of designing of MIS hides significant reserves for essential reduction in cost of these works. The purpose of this work is in offering the generalized (unified) scheme of tasks or subsystems of MIS that will allow to reduce costs for their designing. The conceptual model of the production management system is offered as such scheme. Basic managerial system with a cluster of models of the simplest production systems, managerial system tree, planning feature, function of cost accounting and the idea of polyfunctionality of production information is attributes of the conceptual model. The method of representation of multi-level a production management system as superposition of two-level managerial systems is offered. Two ideas – cluster of models of the elementary production systems and superposition of managerial systems – create prerequisites for classification and typification of the production management systems. The organizational mechanism and the mechanism of aggregating of production information are objects of a first-priority research among attributes of model of the elementary production systems. Classification and typification of the production management systems are a necessary condition for creation universal (or quasiuniversal) the conceptual model of the production management system. The conceptual model of the production management system is considered as a basis for MIS designing.Problems in programming 2017; 2: 48-60